Investigation of Nucleation Kinetics by Nephelometric Measurements. Issue 8 (5th July 2013) - Parisi, M.; Chianese, A.
Abstract The application of a nephelometric probe for investigation of nucleation kinetics is reported. First a check of direct proportionality of the signal with respect to the surface of the solid suspension was performed, followed by an experimental analysis of the nucleation of potassium sulfate crystals from aqueous solutions by applying both polythermal and isothermal methods. The adopted instrument allowed to accurately detect the metastable zone width and the induction time and to monitor the first period of time after nucleation. These latter measurements give an indication of the overall crystal mass evolution at the starting of the crystallization operation.